Application of dodecahedron to describe the switching strategies of asynchronous simulated-moving-bed. (4th January 2017) - Yao, Chuanyi; Jing, Keju; Ling, Xueping; Lu, Yinghua; Tang, Shaokun
Highlights: A dodecahedron was designed to describe and visualize the asynchronous SMB process. The dodecahedron covered all the possibilities of the asynchronous SMB process. The best asynchronous SMB was obtained by optimization based on the dodecahedron. The feed flow rates in the optimized asynchronous SMB were increased by 87% and 15% in the two case studies. Abstract: Among various separation techniques, the simulated moving bed (SMB) process has received special attention, especially the asynchronous SMB that allocates the columns into four zones in a flexible way. With the relative switching times as variables in the Cartesian coordinates system, all applicable switching strategies in asynchronous SMB can be visualized in a dodecahedron with the initial configuration as the origin. Thus, any point in the dodecahedron represents a switching strategy, which could be easily obtained with initial configuration and coordinates. The dodecahedron includes 14 traditional SMB configurations, represented by the 14 vertexes of the dodecahedron. Based on the dodecahedron, the optimization of the asynchronous SMB was conducted through two case studies. Compared to traditional SMB, the feed flow rates were increased by 87% in the enantioseparation of 1, 1′-bi-2-naphthol and 15% in the separation of glucose and fructose without the loss of product purities.